Coursebook Authors on the Role of Literature in Developing Intercultural Competence - Emilia Luukka (CLELEjournal, 2021)
Emilia Luukka's paper reports on Finnish coursebook authors' perspectives and how they see literature in ELT - as contributing to students' intercultural competence, their affective engagement, broadening their perspectives and developing their cognitive capacities.